2022
DOI: 10.1002/brb3.2473
|View full text |Cite
|
Sign up to set email alerts
|

MMP9 SNP and MMP SNP–SNP interactions increase the risk for ischemic stroke in the Han Hakka population

Abstract: Objectives To investigate the association of eight variants of four matrix metalloproteinase (MMP) genes with ischemic stroke (IS) and whether interactions among these single nucleotide polymorphisms (SNPs) increases the risk of IS. Methods Among 547 patients with ischemic stroke and 350 controls, matrix‐assisted laser desorption/ionization time of flight mass spectrometry was used to examine eight variants arising from four different genes, including MMP‐1 (rs1799750), MMP‐2 (rs243865, rs2285053, rs2241145), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“… 64–66 For example, the MMP9 rs17576 polymorphism is associated with an increased risk of IS in the Han Hakka population and interacts with the MMP12 rs660599 polymorphism, further increasing the risk of IS. 67 In addition to the genetic level, MMP9 is also closely related to IS at the protein level. Some studies have found that the level of MMP9 in the serum or plasma of IS patients is elevated and is related to the severity and adverse outcomes of IS.…”
Section: Discussionmentioning
confidence: 99%
“… 64–66 For example, the MMP9 rs17576 polymorphism is associated with an increased risk of IS in the Han Hakka population and interacts with the MMP12 rs660599 polymorphism, further increasing the risk of IS. 67 In addition to the genetic level, MMP9 is also closely related to IS at the protein level. Some studies have found that the level of MMP9 in the serum or plasma of IS patients is elevated and is related to the severity and adverse outcomes of IS.…”
Section: Discussionmentioning
confidence: 99%
“…However, potential limitations of our study deserve consideration. In this study, only 3 SNPs in MMP2 were explored, and we will continue to explore the association of other SNPs in MMP2 , MMPs and gene interactions with IS susceptibility in the future ( 16 ). Additionally, the current study was limited to a single ethnic group, other ethnic groups should be validated in the future ( 13 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The research subjects included 677 patients with IS in the acute phase (within 24 h of onset) and 681 normal individuals, who were recruited from the Affiliated Hospital of Northwest University (Xi'an No.3 Hospital). The inclusion criteria of the IS case group were to use the National Institutes of Health Stroke Scale (NIHSS) to assess the degree of neurological deficit, and to confirm the diagnosis by neurological examination, brain computed tomography (CT) and magnetic resonance imaging (MRI) ( 16 ). Patients with tumors, brain trauma, cerebral hemorrhage and cerebrovascular malformations were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher susceptibility for stroke was also detected for polymorphic variants of another MMPs genes. Assessing SNPs in four genes (rs1799750 in MMP-1 , rs243865, rs2285053, rs2241145 in MMP-2 , rs17576 in MMP-9 , rs660599, rs2276109, and rs652438 in MMP-12 ) and their interactions allows us to detect an association of rs17576 AG and GG genotypes with the increased risk of IS and significant interaction between MMP-9 rs17576 and MMP-12 rs660599 also correlating with the higher risk of IS [ 152 ]. It was observed that SNPs in -1607 1G/2G in MMP-1 and -82 A/G in MMP-12 genes were significantly associated with IS in whole evaluated population, with the -82 A/G polymorphism being a risk factor in European populations and MMP-1 -1607 1G/2G and MMP-12 -82 A/G in African populations [ 153 ].…”
Section: Role Of Mmps In Cardioembolic Strokementioning
confidence: 99%